The 1918 Influenza Pandemic and Its Lessons for COVID-19 - Beach, Brian; Clay, Karen; Saavedra, Martin (Journal of Economic Literature, 2022)
This article reviews the global health and economic consequences of the 1918 influenza pandemic, with a particular focus on topics that have seen a renewed interest because of COVID-19. We begin by providing an overview of key contextual and epidemiological details as well as the data that are available to researchers. We then examine the effects on mortality, fertility, and the economy in the short and medium run. The role of non-pharmaceutical interventions in shaping those outcomes is discussed throughout. We then examine longer-lasting health consequences and their impact on human capital accumulation and socioeconomic status. Throughout the paper we highlight important areas for future work. (JEL E24, E32, I12, I15, J13, J24, N30)